Exploring classical Chinese poetry with AI Tool in PPT design / Chong Peng Hwa, Choo Kim Fong and Toh Ling Ling - Peng Hwa, Chong; Kim Fong, Choo; Ling Ling, Toh (Faculty of Computer and Mathematical Sciences, 2023)
This initiative product is created at the intersection of cultural heritage and technological innovation and aims to bridge the gap between the timeless appeal of classical Chinese poetry and contemporary methods of presentation. This work addresses the need for a transformative solution to presentation design considering the difficulty of properly conveying the depth of linguistic and cultural complexity contained in these poems. The main goals of the initiative are to improve the visual appeal of PowerPoint presentations by incorporating AI-generated design elements and accurately conveying the emotional resonance, cultural significance, and historical context of each poem within the presentation. The result of this combination is a set of PowerPoint slides that incorporate artificial intelligence (AI) to make design recommendations, harmonies colour, and enhance layouts. These features are seamlessly integrated with carefully curated text content. This innovative method offers a unique advantage by increasing viewers’ visual engagement while successfully conveying the complex essence of classical Chinese poetry. The results of the study show that integrating artificial intelligence (AI) into PowerPoint design (PPT) provides an interactive and engaging approach to exploring and appreciating the aesthetic qualities of this form of artistic expression. This integration also facilitates deeper cross-cultural understanding and engagement. In summary, the integration of artificial intelligence (AI) technology with the rich heritage of classical Chinese poetry represents a coherent fusion of traditional and innovative elements. The combination offers a modern way to access and present cultural treasures of both historical and contemporary eras in an interactive and enlightening way.